Design and Implementation a Smart System for Monitoring the Electrical Energy based on the Internet of Things - Nabaa Ali Jasim; Haider ALRkabi (Wasit Journal of Engineering Sciences)
In this article, an open source monitoring system based on  Internet of Thing (IoT) is designed to monitor electrical energy consumption. This system provides real-time information about energy consumption over time. To implement this system, sensors were used to measure data, a Raspberry as an application server to display and store data, and microcontrollers to collect information. The process of data transfer via the Internet using the Message Queuing Telemetry Transport (MQTT (protocol between the microcontroller and the server. Through the experimental results obtained from the proposed system, the voltage, current, active power and power consumption were successfully recorded.